Love on the Margins: The Effects of Social Stigma and Relationship Length on Romantic Relationship Quality. (January 2014) - Doyle, David Matthew; Molix, Lisa
National data on romantic relationships reveal a prominent gap between members of devalued and dominant groups in the United States, with devalued group members experiencing less positive relationship outcomes. However, little research examines how social stigma affects relationship quality for members of devalued groups and moderating factors have generally not been explored in the literature. In the current studies, we experimentally examined the effects of social stigma on relationship quality among women (Study 1) and African Americans (Study 2) as well as whether these effects differed based upon relationship length (Studies 1 and 2). Results showed that individuals involved in shorter relationships reported lesser relationship quality after social stigma was made salient, while those involved in longer relationships reported somewhat greater relationship quality after social stigma was made salient. Implications for future research on social stigma and relationship quality as well as moderating factors are discussed.